Biological pre-treatments enhance gravity-driven membrane filtration for the decentralized water supply: Linking extracellular polymeric substances formation to flux stabilization. (1st October 2018) - Tang, Xiaobin; Ding, An; Pronk, Wouter; Ziemba, Christopher; Cheng, Xiaoxiang; Wang, Jinlong; Xing, Jiajian; Xie, Binghan; Li, Guibai; Liang, Heng
Abstract: Gravity-driven membrane (GDM) filtration is a promising technology for decentralized drinking water treatment due to its low energy requirements and simple operation. The reduced flux observed in GDM systems relative to other membrane treatment techniques remains a vital obstacle to their wider application. With the goal of further improving membrane flux and permeate quality, three simple and practical technologies have been examined as pre-treatments for GDM systems, (i) slow filtration with granular activated carbon (GAC), expected to remove both biodegradable and non-biodegradable contaminants, (ii) slow filtration with modified fiber ball (MFB), expected to promote biodegradation of organic compounds and (iii) microfiltration (MF), expected to reject suspended substances and particles. Results indicated that stable permeability increased by approximately 230%, 150% and 100% in GDM systems employing GAC, MFB and MF pre-treatments compared to the control. The dissolved organic compounds (DOC) were removed by approximately 60% and 30% in GAC/GDM and MFB/GDM, while MF/GDM and GDM control were not effective at DOC removal. Correlations between the stable flux and extracellular polymeric substances (EPS) concentration (R 2 > 0.9) indicated that reduction of EPS should be responsible for the flux improvements. Tracing the fate of florescent foulants illustrated that the EPS was mainly secreted/converted by the microbes colonizing within the bio-fouling layer of the GDM system. During long-term filtration, assimilable organic compounds (AOC) which can serve as nutrients for the growth of microbes within the bio-fouling layer were efficiently consumed (>50%) by the biological pre-treatments. This reduction in AOC was linked with a reduction in the growth/activity of bacteria within the bio-fouling layer of GDM system and a reduction in EPS accumulation. Overall, biological pre-treatments can significantly enhance the flux and water quality produced by a GDM system without significantly increasing the operation and maintenance. These improvements in flux and water quality can hopefully spark wider adoption of GDM as an economical and environmentally-friendly technology for decentralized drinking water treatment. Highlights: An environmentally-friendly and sustainable biological drinking water process was proposed. Stable permeability of GDM process was improved by 100–230% by biological pre-treatments. EPS was reduced by 40–60% by pre-filters of granular activated carbon and modified fiber balls. Biological pre-treatments reduced EPS accumulation by limiting the bio-activity/growth. A good correlation between stable flux and EPS concentration was observed (R 2 > 0.9).